Сombination desquamative glossitis and burning mouth syndrome in practice dentists (LLC "Endo Press", 2020)
Desquamative glossitis widespread language of defeat. Some patients complain of pain and burning sensation in the tongue, worse when taking irritating foods. In recent years we note the increase in the number of patients with a combination of desquamative glossitis and burning mouth syndrome. Literature data on the pathogenesis of these diseases suggest the similarity of risk factors for this disease.The study of the psychological state of patients with a combination of desquamative glossitis and burning mouth syndrome revealed the presence of clinically significant anxiety, severe subclinical depression.